Politics, religion and the British revolutions : the mind of Samuel Rutherford - Coffey, John, 1969- (Cambridge studies in early modern British history., 1997)
This is the first modern intellectual biography of the Scottish Covenanters' great theorist Samuel Rutherford (c. 1600-61). The central focus is on Rutherford's political thought and his major treatise, Lex, Rex, written in 1644 as a justification of the Covenanters' resistance to King Charles I. The book demonstrates that while Lex, Rex provided a careful synthesis of natural-law theory and biblical politics, Rutherford's Old Testament vision of a purged and covenanted nation ultimately subverted his commitment to the politics of natural reason. The book also discusses a wide range of other topics, including scholasticism and humanism, Calvinist theology, Presbyterian ecclesiology, Rutherford's close relationships with women and his fervent spirituality. It will therefore be of considerable interest to a range of scholars and students working on Scottish and English history, Calvinism and Puritanism, and early modern political thought.